DÁSTANLARDA TUWÍSQANLÍQ QARÍM-QATNASLARǴA BAYLANÍSLÍ SÓZLERDIŃ QOLLANÍLÍWÍ («HÚRLIQA–HÁMIRE» DÁSTANÍ MÍSALÍNDA) - Abdiev, A. (SCIENCE and SOCIETY, 2023)
This article studies the terms of kinship in the Karakalpak language, their similarities and differences. We discussed the division of kinship terms into groups, their linguogeographical and linguocultural aspects, and discussed them on the basis of scientific sources.